2022
DOI: 10.1186/s12912-022-00813-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cervical screening and HPV vaccination attendance of Roma women in Hungary: community nurse contribution is key

Abstract: Background HPV screening/vaccination has been observed lower for ethic minorities. Understanding factors that predict and can improve attendance is therefore key. Hence, the aim was to identify causes, especially concerning the quality of the patient-provider relationship, that predict past HPV screening and vaccination turnout of Roma women in Hungary. Methods Cross-sectional research design with self-developed, culturally sensitive questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In this study, migrant women who reported having had a bad experience in CCS in the past were less likely to be CCS non-attenders. This seems contrary to evidence suggesting that negative experiences during screening are more likely to increase non-attendance among women [7,24,34,35]. Considering that this is a cross-sectional study, this finding may be explained by reverse causality.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, migrant women who reported having had a bad experience in CCS in the past were less likely to be CCS non-attenders. This seems contrary to evidence suggesting that negative experiences during screening are more likely to increase non-attendance among women [7,24,34,35]. Considering that this is a cross-sectional study, this finding may be explained by reverse causality.…”
Section: Discussioncontrasting
confidence: 99%
“…Ezért szükség van a helyi szükségleteknek megfelelő célzott intervenciókra az egészségügyi alapellátásban, a házorvosok, védőnők, a közösségi ápolók fokozottabb részvételére a szűréssel kapcsolatos egészségkommunikációban. Ezzel elősegíthető, hogy a lakosság a megfelelő információn alapuló tudatos döntést tudjon hozni a szűrésen való részvételről és az oltás beadásáról, különös tekintettel a nehezen elérhető hátrányos helyzetű, kistelepüléseken élő, és az etnikai kisebbégekhez tartozók számára (Pakai et al, 2022;Pakai et al, 2018;Pakai et al, 2017). 2016-ban bevezetésre került a nonavalens HPV oltás, mely 7 hrHPV (16,18,31,33,45,52,58)…”
Section: Genotípus Szerinti Prevalenciaunclassified
“…Therefore, it is crucial to focus on the health needs of national minorities, especially Hungarian-speaking Roma women in Romania and Slovakia. As women, they play significant roles in maintaining family health and serve as important role models ( 26 , 32 , 46 , 47 ).…”
Section: Introductionmentioning
confidence: 99%